I simply read the question first: A Narrative Inquiry into Pre-service English Teachers’ Strategies on IELTS reading comprehension - Beny Hamdani; Haida Umiera Hashim (Eduvelop: Journal of English Education and Development, 2025)
A huge number of studies on reading strategies have been carried out in relation to reading proficiency levels. The conflicting findings and rarity of studies concerning the use of reading comprehension strategies in English testing become the impetus to conduct a further study on reading comprehension strategies issues. The recent research aims to delve into Indonesian pre-service English teachers' reading strategies and how these reading strategies enhance their reading comprehension on IELTS. This study employs a narrative study and uses in-depth semi-structured interviews to collect the data. There are six Indonesian pre-service English teachers involved as research participants, and they were periodically interviewed for adequate data regarding their reading comprehension strategies. The follow-up interview was performed throughout data collection until data saturation was achieved, and the data were then analyzed qualitatively by transcribing, coding, categorizing, and thematizing to find out the emerging themes concerning reading comprehension strategy. The results reveal that there are four themes, namely vocabulary mastery, activating background knowledge, test-taking strategies, and appropriate institutional policies. The results of this study can be used as a reference to foster reading comprehension on IELTS. Suggestion for further research is discussed at the end of this research.